Influência de diferentes materiais e técnicas restauradoras na carga máxima de carregamento em molares tratados endodonticamente - Bromberg, Carolina Ritter (2016)
Objectives: The aim of this in vitro study was to compare the maximal load resistance of endodontically treated molars restored with: inlays or onlays of Lava Ultimate, composite resin Z350 XT with or without fiberglass post. Methods: Fifty sound extracted third molars were embedded in acrylic resin and divided into 5 groups (n = 10 per group): H = healthy, ON = onlay, IN = inlay, RC = composite resin, PT = fiberglass post + Z350 XT. The MOD preparations and endodontic treatment were performed. Indirect restorations were made through CAD/CAM CEREC system and cemented with SingleBond Universal and RelyX Ultimate under load of 1 kg. Restorations of RC and PT groups were performed by incremental technique and the two posts in the PT group were horizontally transfixed and bonded with flowable resin. Then, mechanical loading in all samples were performed in 500.000 cycles at 200 N at a frequency of 1 cycle / second and the maximum load test was performed in a universal testing machine at a speed of 1 mm / min. After the mechanical test, the faults were categorized into pulpal floor fracture (irreparable) and cuspal fracture (repairable). Results: Mean values were (means followed by the same letter show no significant difference to ANOVA and Tukey): RC 1680N ± 454 d; PT 2693N ± 372 bc; ON 2922N ± 774 b; IN 2053N ± 313 cd; H 4514N ± 548 a. The predominant failure pattern for teeth restored with onlays, inlays and direct composite resin with or without post was the irreparable type. Conclusion: Endodontically treated molars restored with transfixed fiberglass post and composite resin have similar fracture resistance to those restored with indirect Lava Ultimate inlay and onlay. Horizontally fiber post restoration has the same efficiency that onlays restoration.